Journeys through ADDulthood : discover a new sense of identity and meaning while living with attention deficit disorder - Solden, Sari. (New York : Walker & Co., 2002)
Looks at the challenges faced by adults with AD/HD and offers information on the symptoms, treatment, and ways to organize and protect oneself in the world.
Includes bibliographical references (p. [279]-285) and index.
Keywords: Attention-deficit hyperactivity disorder in adults; People with attention-deficit hyperactivity disorder